INDICATORS FOR DEPRESSION AMONG ELDERLY IN LONG-TERM CARE INSTITUTIONS - Dâmarys Kohlbeck de Melo Neu; Maria Helena Lenardt; Susanne Elero Betiolli; Tatiane Michel; Mariluci Hautsch Willig (Universidade Federal do Paraná, 2011)
A quantitative transversal descriptive study, whose objective was to identify indicators for depression among elderly residents in a Long-term Care Home for the Elderly in Curitiba, Paraná. The institution is home to 78 elderly residents of both sexes with differing degrees of dependency. The sample was made up of 21 elderly persons after cognitive screening and application of inclusion and exclusion criteria. Data was collected via a multidimensional questionnaire BOAS (Brazil Old Age Schedule) and analysed by descriptive statistics and frequency distribution. Of the sample, 57.14% presented no markers for depression; 28.57% had mild depression: and 14.29% had severe depression. It is inferred that they presented a higher level of depressive symptomatology, however, the diagnosis of depression is not referred to. Early detection of these symptoms helps to avoid the development of this pathology and prevent its effects on health and quality of life among the elderly.